Polityka wewnętrzna ChRL jako czynnik w relacjach chińsko-indyjskich - Okraska, Tomasz (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Internal policy of the PRC as a factor in Sino‑Indian relations The article focuses on the analysis of internal factors of Chinese foreign policy, paying particular attention to their impact on Sino‑Indian relations. It addresses the question of making China policy, the impacts of actors such as the military and the various factions within the Communist Party of China. Has been widely discussed topic of Chinese nationalism and its current and potential impact on policy making in the PRC. The author pays particular attention to the changes in the Chinese policy, which take place after the adoption of state power by Xi Jinping in 2012. Xi tries to be a strong leader, and be able to concentrate in his hand more power than its predecessors. Both intended and unexpected effects of their actions can have a significant impact on China’s policy towards India and other countries. Reflections in the article refer often to the history of Middle Kingdom, because China has a great sense of historicity of their own civilization. No coincidence that one of the most frequently cited in discussions on China’s foreign policy is an ancient strategic treatise “The Art of War” by Sun Tzu. Key words: China, India, foreign policy, nationalism, role of the army